(untitled) (Journal of Informatics and Mathematical Sciences, 2014)
The boundedness nature is considered in this paper for positive solutions of a max-type fourth order difference equation with periodic coefficients. A series of sufficient conditions are obtained to ensure the existence of bounded and unbounded solutions to this equation.